Co-movement of cryptocurrencies and African stock returns: A multiresolution analysis - Seyram Pearl Kumah; Jones Odei-Mensah; Richmell Baaba Amanamah (Cogent Business & Management, 2022)
This paper investigates the co-movement between cryptocurrencies and African stock returns to uncover their degree of association and global portfolio diversification benefits implementing the three-dimensional continuous Morlet wavelet transform technique. Data span 10 August 2015 to 10 December 2021 at daily frequency. The results suggest high degrees of co-movement between the asset markets at medium and lower frequencies implying that stock markets in Africa are highly exposed to cryptocurrency market disruptions from the medium term and that international investors seeking to hedge their price risk in African stock markets using cryptocurrencies may have to look at the short term. The phase difference arrow vectors implying lead (lag) effects are time-varying and heterogeneous showing no particular cryptocurrency or stock market as leader or follower. Different markets have the potential to lead or lag other markets at varying scales which may induce arbitrage opportunities for international and local investors. Our findings provide insights for policymakers, regulators and international investors as an economy's monetary policy can be affected by the connections between the domestic capital market and other markets globally.
Keywords: G15; G11; C22; G32; 650; cryptocurrencies; Co-movement; African stocks; Wavelet coherency